Toxicity of four sulfonamide antibiotics to the freshwater amphipod Hyalella azteca. (22nd February 2013) - Bartlett, Adrienne J.; Balakrishnan, V.K.; Toito, J.; Brown, L.R.
Abstract: Sulfonamides are a widely used class of antibiotics; however, there are few toxicological data available with which to conduct environmental risk assessments for these compounds. Therefore, the toxicity of four sulfonamides (sulfaguanidine, sulfathiazole, sulfamerazine, and sulfasalazine) to Hyalella azteca was assessed in chronic (four‐week), water‐only exposures. Survival was evaluated weekly, and growth was measured at the end of the test. Four‐week lethal concentrations associated with 50% mortality (LC50s) for sulfaguanidine, sulfathiazole, and sulfamerazine were 0.90, 1.6, and 3.9 µM, respectively. Sulfaguanidine caused effects on survival more quickly and at lower concentrations than sulfathiazole or sulfamerazine. These differences were more pronounced at week 1 than week 4, when sulfaguanidine LC50s were 8 to 20 times lower and 2 to 4 times lower, respectively. Growth was affected by sulfathiazole but was a less sensitive end point than survival, with an effective concentration associated with 50% reduction in growth (EC50) of 13 µM, whereas sulfaguanidine and sulfamerazine caused negligible effects on growth. Sulfasalazine had no effect on survival or growth at any concentration tested, up to 13 µM. The effects observed in the present study occurred at concentrations exceeding those typically found in environmental waters. However, given that LC50s decreased with exposure duration (except for sulfasalazine), the present study demonstrates the importance of conducting longer‐term tests to adequately assess the environmental toxicity of sulfonamides. Environ. Toxicol. Chem. 2013;32:866–875. © 2013 SETAC